Analysis of Thermal Energy in the Drying Process of Taro Tubers (Colocasia esculenta (L.)) using a Rack-Type Dryer - Nurul Aen; Rahmat Sabani; Ida Ayu Widhiantari (Jurnal Online Pertanian Tropik, 2024)
Repok Pidendang Hamlet is one of the hamlets in the Pemepek Village area, Pringgarata District, Central Lombok Regency which has a superior agricultural commodity, one of which is the taro plant. An important problem faced by the people of Repok Pindendang Hamlet is the abundant taro harvest but still lacks in processing, causing taro to spoil quickly. Therefore, it is necessary to process taro that can increase the shelf life and quality of taro. This study aims to analyze the energy balance in the drying process of taro tubers (Colocasia esculenta (L.)) in a rack-type dryer. The method used is an experimental method using an energy equilibrium approach. The material used is taro tubers with a thickness of I mm which will be dried with temperature variations of 40-45°C, 50-55°C and 60-65°C until the moisture content is constant. The results show the amount of heat energy in, useful heat energy, outgoing heat energy, lost heat energy, and the highest number of enthalpy were obtained at 60-65°C temperature treatment, which were 1719.72 kJ, 869.59 kJ, 823.98 kJ, 1693.57 kJ, and 304.82 kJ/kg, respectively. The total efficiency of the drying system during drying using rack-type dryers was obtained at a temperature of 60-65°C of 50.56% and the lowest efficiency was found at a temperature of 50-55°C of 24.26%.